Ginseng: A dietary supplement as immune-modulator in various diseases - Riaz, M; Rahman; Zia-Ul-Haq, M; Jaffar, HZE ; Manea, R (ELSEVIER SCIENCE LONDON84 THEOBALDS RD, LONDON WC1X 8RR, ENGLAND, 2019)
Background: Mechanistic studies suggest that ginseng, as dietary supplement, plays a key role in disease prevention by modulating the immune function of human body. The root of Panax ginseng and Panax quinquefolius (Family: Araliaceae) are commonly known as 'ginseng'. Ginseng roots are well known for their high content of saponins, ginsenosides, phenolic compounds, including carbohydrates and carotenoids. In recent years, there is a growing interest in the role of ginseng as a nutraceutical or functional food with increasing market value. Extracts and bioactive compounds isolated from ginseng are studied for their various health promoting activities such as antioxidant, antitumor, antihyperglycemic, skin protecting, anti-osteoporotic anticancer, anti-infective and respiratory problems. Scope and approach: The present review reports structural and functional diversity of ginseng, key bioactive compounds, their immunity boosting potential and studies related to cell mediated and humoral immunity of ginseng. Immunity-boosting power of ginseng against cancer, autoimmune diseases and viral and bacterial infections has been compiled. The vaccine adjuvant role, safety profile and drug interactions ginseng and derived products are also discussed. Nano-ginseng as immune modulators has been a unit of article. The clinical trials carried out and patent portfolio of ginseng against immune disorders is the important section of this article. Patent search was performed by using The Patent Lens search engine and results included under heading "Ginseng based Patents for immunomodulation". Key isolated compounds have been mentioned along with their structures to give a quick overview of the chemical constituents. Key findings and conclusions: After critically reviewing the immune potential of ginseng both in vitro and in vivo and even describing the clinical data in humans we reached at conclusion that ginseng can be considered as good candidates for the development of novel functional foods that has natural potential to modulate immunity against various diseases. Future work will have to focus on the identification of the relevant compounds from ginseng, the thorough preclinical characterization and selection of the candidate bioactives, and the rational design of immunotherapy studies involving objective as well as subjective parameters for measuring clinical efficacy. We believe that this review will be a valuable resource for more studies on ginseng as a dietary supplement in relevance to immune-modulation.